A hydrocracking catalyst, its preparation method and use
Patent Information
- Application Number
- CN202410478372.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-19
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-04-19
AI Technical Summary
该活性金属含量较低,孔分布主要集中在4~10nm,催化剂的加氢活性不足,得到的柴油馏分中芳烃含量不达到工业级白油产品的标准
[0050] 1. The hydrocracking catalyst of the present invention comprises a support and an active metal component, wherein the support comprises alumina and modified Y molecular sieve; the active metal component comprises Mo and Group VIII metal elements; the Mo comprises +5 valence Mo; the Group VIII metal elements exist in the catalyst in the form of metal phosphides.
Smart Images

Figure BDA0004801138390000131 
Figure BDA0004801138390000132 
Figure BDA0004801138390000141
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrocracking catalyst preparation, specifically relating to a hydrocracking catalyst, its preparation method, and its application in the production of specialty oils. Background Technology
[0002] Hydrocracking technology is one of the important heavy oil deep processing technologies in modern oil refining and petrochemical industries. It features strong feedstock adaptability, high product flexibility, high selectivity for target products, good product quality, and high added value. It can directly convert various heavy and low-quality feedstocks into clean fuel oil and high-quality chemical feedstocks, making it the core of modern refining and chemical enterprises' oil-chemical-fiber integration. Hydrocracking units have become a "standard configuration" in refining and chemical enterprises and are increasingly widely used both domestically and internationally.
[0003] Hydrocracking diesel fractions are characterized by their water-white color, low impurity content, and high saturated hydrocarbon content, and can be blended to produce various white oils, rust-preventive oils, transformer oils, and aluminum cold-rolling oils. Compared with conventional hydrocracking products such as refined oils and chemical raw materials, transformer oils and industrial white oils have much stricter requirements regarding low-temperature fluidity and aromatic hydrocarbon content. Depending on the grade, industrial white oils have a pour point range of -3 to -9°C, and an aromatic hydrocarbon content of no more than 5%. Transformer oils, depending on the lowest cold-state operating temperature in actual applications, have a pour point range of -10°C to -50°C, and a polycyclic aromatic hydrocarbon content of less than 3%. Similarly, lubricating oil base oils also have corresponding requirements regarding pour point and viscosity index (related to aromatic hydrocarbons). This necessitates that hydrocracking catalysts possess both high isomerization performance and high aromatic hydrocarbon conversion capacity.
[0004] CN103055927A discloses a method for preparing a hydrocracking catalyst. The method is as follows: An acidic mixed solution A containing a hydrocracking active metal and silicon is prepared; an alkaline solution B of sodium aluminate is prepared; a portion of the alkaline solution B is added to the acidic mixed solution A; then CO2 gas is introduced, and this step is repeated 1-6 times. A suspension of Y-type molecular sieve is then added and mixed thoroughly. The mixture is aged, filtered, dried, shaped, washed, dried, and calcined to obtain the hydrocracking catalyst. This method can increase the pore volume and specific surface area of the catalyst. However, the increase in pore volume and specific surface area and the improvement in the dispersion of the active catalyst metal are limited, relying solely on the carbonate generated during precipitation and the gas released during calcination. The metal oxide particles are relatively large, which can easily cause the active metal in the catalyst to aggregate, thus affecting the catalytic performance.
[0005] CN102039151A discloses a method for preparing a hydrocracking catalyst. The method is as follows: amorphous silica-alumina and Y zeolite are mixed evenly, then a binder is added, kneaded, and rolled into briquettes. The briquettes are then extruded to obtain a support, which is then loaded with a hydrogenation active metal. The amorphous silica-alumina is prepared by a carbonization method. However, this active metal has a low content, and the pore distribution is mainly concentrated in the 4–10 nm range. The catalyst's hydrogenation activity is insufficient, and the aromatic content in the resulting diesel fraction does not meet the standards for industrial-grade white oil. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a hydrocracking catalyst, its preparation method, and its applications. This catalyst exhibits excellent isomerization properties and aromatic hydrocarbon conversion capabilities, making it suitable for hydrocracking processes used in the production of specialty oils and lubricating oil base oils.
[0007] The first aspect of this invention provides a hydrocracking catalyst, comprising a support and an active metal component. The support comprises a modified Y molecular sieve and alumina. The modified Y molecular sieve has the following properties: a crystal particle size of less than 500 nm, preferably 300–500 nm; a molar ratio of silicon oxide to alumina of 8–55; and a specific surface area of 640–800 m². 2 / g, with cell parameters of 2.433–2.460 nm and average pore size of 10–30 nm.
[0008] According to the present invention, the sodium content in the modified Y molecular sieve is less than 1 wt%.
[0009] According to the present invention, the content of modified Y molecular sieve is 50% to 80% and the content of alumina is 15% to 48% based on the mass of the support. Furthermore, the support also contains Ga, and the content of Ga is 2.0% to 5.0% based on the mass of the support, calculated as Ga₂O₃.
[0010] According to the present invention, the active metal component includes Mo and a Group VIII metal element; the Mo includes +5 valence Mo; the Group VIII metal element exists in the catalyst in the form of a metal phosphide.
[0011] According to the present invention, the catalyst further includes +4 valent Mo and +6 valent Mo.
[0012] According to the present invention, in the catalyst, +5 valence Mo accounts for more than 50% of the total Mo atomically, preferably 55% to 80%. As a non-limiting example, +5 valence Mo accounts for any value of 65%, 68%, 70%, 72%, 75%, or 78% of the total Mo atomically.
[0013] According to the present invention, in the catalyst, the sum of +4 valence Mo and +6 valence Mo accounts for 20% to 45% of the total Mo atoms. More preferably, in the catalyst, +4 valence Mo accounts for 10% to 43% of the total Mo atoms; and +6 valence Mo accounts for 2% to 10% of the total Mo atoms. As a non-limiting example, +4 valence Mo accounts for any value of 15%, 20%, 22%, 25%, 32%, 35%, 38%, or 40% of the total Mo atoms; and +6 valence Mo accounts for any value of 4%, 6%, 8%, or 9% of the total Mo atoms.
[0014] According to the present invention, in the catalyst, +5 valence Mo is preferably molybdenum pentachloride; +4 valence Mo is preferably molybdenum disulfide; and +6 valence Mo is preferably molybdenum oxide.
[0015] According to the present invention, the group VIII metal element is selected from one or more of Fe, Co, and Ni, preferably at least one of Co and Ni, and more preferably Ni.
[0016] According to the present invention, based on the mass of the catalyst, the mass content of the support is 50% to 90%, the content of Group VIII metals as oxides is 1% to 10%, and the content of molybdenum as oxides is 5% to 40%.
[0017] According to the present invention, the catalyst has the following properties: a specific surface area of 400–750 m². 2 / g, pore volume is 0.3~0.9mL / g, mechanical strength is 120~180N / cm, total infrared acid content is 0.3~0.7mmol / g, and the ratio of B acid content to L acid content is 7.5~15.2.
[0018] According to the present invention, the pore size distribution of the catalyst is as follows: the pore volume of pores with a diameter <10 nm accounts for 23% to 28% of the total pore volume, the pore volume of pores with a diameter of 10 to 20 nm accounts for 38% to 45% of the total pore volume, and the pore volume of pores with a diameter >20 nm accounts for 27% to 39% of the total pore volume.
[0019] A second aspect of the present invention provides a method for preparing the above-mentioned hydrocracking catalyst, comprising:
[0020] (1) A first impregnation solution is obtained by mixing molybdenum source, sulfur source and water, and then impregnated on a support. After drying, catalyst intermediate I is obtained.
[0021] (2) React the catalyst intermediate I described in step (1) with chlorine gas to obtain catalyst intermediate II;
[0022] (3) The catalyst intermediate II described in step (2) is impregnated with a second impregnation solution containing nickel and phosphorus sources, and then cured, dried and calcined to obtain the catalyst.
[0023] According to the present invention, in step (1), the support comprises modified Y molecular sieve and alumina. The method for preparing the support includes:
[0024] (11) NaY molecular sieve is exchanged with ammonium ions, filtered and washed to obtain NH4Y molecular sieve filter cake;
[0025] (12) The NH4Y molecular sieve filter cake obtained in step (11) is mixed with organic acid, water-soluble polymer and water, and then subjected to hydrothermal treatment to obtain modified Y molecular sieve.
[0026] (13) The modified Y molecular sieve, pseudoboehmite, adhesive, pore expander and water obtained in step (12) are mixed and kneaded, dried and calcined to obtain the catalyst support intermediate.
[0027] (14) The catalyst support intermediate obtained in step (13) is immersed in gallium nitrate solution and treated with high temperature steam to obtain the support.
[0028] According to the present invention, in the preparation method of the carrier, the properties of the NaY molecular sieve in step (11) are as follows: the molar ratio of silicon oxide to aluminum oxide is 3 to 7:1, and the sodium content is 6 wt% to 12 wt%.
[0029] According to the present invention, in the preparation method of the carrier, step (11) of ammonium ion exchange of NaY molecular sieve can be carried out by conventional methods, that is, NaY molecular sieve and ammonium salt solution are mixed and slurried, the pH value of the slurry is adjusted (the pH value can be adjusted by at least one of nitric acid or hydrochloric acid), ammonium ion exchange is carried out, and after filtration and washing, NH4Y molecular sieve filter cake is obtained. The mass ratio of NaY molecular sieve:water:ammonium salt is 1:6-25:0.2-0.4; the pH value of the slurry is adjusted to 3-4; the ammonium ion exchange temperature is adjusted to 70-90℃; the ammonium ion exchange time is 2-4 hours; and the number of ammonium ion exchanges is 1-3 times. The ammonium salt can be one or more of ammonium chloride, ammonium nitrate, ammonium sulfate, and ammonium phosphate.
[0030] According to the present invention, in the method for preparing the carrier, the filtration and washing in step (11) can be carried out by conventional methods, and the washing can be carried out by deionization washing.
[0031] According to the present invention, in the method for preparing the carrier, the organic acid in step (12) is selected from at least one of fumaric acid, adipic acid, tartaric acid, citric acid, oxalic acid, acetic acid, salicylic acid, and malic acid. The water-soluble polymer is selected from at least one of polyvinyl alcohol, polyethylene oxide, polyvinylpyrrolidone, and water-soluble polysaccharides (such as methylcellulose). The weight-average molecular weight of the water-soluble polymer is 10,000 to 40,000.
[0032] According to the present invention, in the preparation method of the carrier, the mass ratio of NH4Y molecular sieve in step (12) based on NaY in step (1): organic acid: water-soluble polymer: water is 1:0.01~0.05:0.05~0.25:15~40.
[0033] According to the present invention, in the method for preparing the carrier, the hydrothermal treatment conditions in step (12) are as follows: temperature is 100-150℃, and treatment time is 5-12h. The heating rate is 8-15℃ / min. Preferably, the hydrothermal treatment employs a two-stage process, with the second stage temperature at least 15℃ higher than the first stage temperature, preferably at least 20℃ higher. The hydrothermal treatment is generally carried out in a sealed high-pressure reactor under autogenous pressure. After the hydrothermal treatment in step (12), drying is performed under the following conditions: drying temperature is 100-160℃, and drying time is 3-8 hours.
[0034] According to the present invention, in the method for preparing the carrier, the mass ratio of the pseudoboehmite (calculated as alumina) to the modified Y molecular sieve in step (13) is (7-13):(15-30). The adhesive can be at least one of nitric acid, acetic acid, and citric acid. An extrusion aid can be added according to the molding requirements of the present invention; the extrusion aid can be guar gum powder. The pore-expanding agent can be one or more of graphite, activated carbon, sawdust, or cellulose. The amount of adhesive, extrusion aid, and water added is added according to the actual molding requirements; the present invention has no particular requirements. The amount of pore-expanding agent added is 2wt% to 10wt% of the total mass of the pseudoboehmite (calculated as alumina) and the modified Y molecular sieve.
[0035] According to the present invention, in the method for preparing the carrier, the molding can be carried out using conventional molding methods, such as extrusion molding, tablet molding, etc.
[0036] According to the present invention, in the method for preparing the carrier, the drying temperature in step (13) is 120-160°C, the drying time is 3-6 hours, the calcination temperature is 550-700°C, and the calcination time is 2-6 hours.
[0037] According to the present invention, in the method for preparing the carrier, the concentration of the gallium nitrate solution in step (14) is 0.5–2.5 mol / L. The impregnation method in step (14) is saturated impregnation or unsaturated impregnation. The conditions for the high-temperature steam treatment are as follows: temperature 500–700°C, time 60–90 min. Further, drying may or may not be performed before the high-temperature steam treatment. When drying is performed, the drying conditions are constant temperature at 100–140°C for 2–6 hours.
[0038] According to the present invention, in the method for preparing the catalyst, the molybdenum source in step (1) is selected from at least one of ammonium dimolybdate, ammonium tetramolybdate dihydrate, and ammonium heptamolybdate tetrahydrate; the sulfur source is selected from at least one of thiourea, ammonium sulfide, thioacetamide, and sodium thiosulfate; the mass ratio of the molybdenum source to the sulfur source is 3-5:2-4. In the first impregnation solution, the mass content of the molybdenum source is 25wt%-45wt%.
[0039] According to the present invention, in the method for preparing the catalyst, the impregnation in step (1) can be carried out by spray impregnation, and the impregnation can be carried out by saturated impregnation or supersaturated impregnation. The drying conditions are drying at 100-140°C for 4-8 hours.
[0040] According to the present invention, in the method for preparing the catalyst, in step (2), the purity of the chlorine gas is 96% or higher by volume fraction. The flow rate of the chlorine gas is 2.7 to 6.8 mL / (min·g catalyst intermediate I); and / or, the reaction conditions are as follows: the reaction temperature is 300 to 400 °C, and the reaction time is 40 to 90 min.
[0041] According to the present invention, in the method for preparing the catalyst, the nickel source in step (3) is a soluble salt, such as at least one of nitrates, monohydrogen phosphates, and dihydrogen phosphates; the phosphorus source is selected from at least one of ammonium phosphates, sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, and phytic acid. In the second impregnation solution, the molar ratio of the nickel source (based on metal element) to the phosphorus source (based on phosphorus element) is 0.3 to 3:1. In the second impregnation solution, the mass content of the nickel source is 40 wt% to 60 wt%.
[0042] According to the present invention, in the preparation method of the catalyst, the impregnation in step (3) can be carried out by spray impregnation, and the impregnation can be carried out by saturated impregnation or supersaturated impregnation.
[0043] According to the present invention, in the method for preparing the catalyst, the conditioning in step (3) involves placing the impregnated sample under sealed conditions at 10–30°C for 6–12 hours. The conditioning pressure is not particularly limited and can be autogenous pressure. And / or, the drying conditions are drying at 100–160°C for 1–8 hours. The calcination conditions are calcination at 480–550°C for 4–8 hours. The drying atmosphere is an oxygen-containing atmosphere. The calcination atmosphere is selected from any one of a nitrogen atmosphere, an inert gas atmosphere, a hydrogen / nitrogen atmosphere, and a hydrogen / inert gas atmosphere, wherein the hydrogen gas fraction in the hydrogen / nitrogen atmosphere and the hydrogen / inert gas atmosphere is 5%–50%.
[0044] According to the present invention, in the method for preparing the catalyst, the catalyst in step (3) has the following properties: a specific surface area of 400–750 m². 2 / g, pore volume is 0.3~0.9mL / g, mechanical strength is 120~180N / cm, total acid content is 0.3~0.7mmol / g, and the ratio of B acid content to L acid content is 7.5~15.2.
[0045] The third aspect of this invention provides the application of the above-described hydrocracking catalyst or the hydrocracking catalyst prepared by the above-described preparation method in the hydrocracking process of base oils for producing specialty oils and lubricating oils from vacuum distillate oil.
[0046] According to the present invention, the application conditions are: reaction temperature of 350–480°C; reaction pressure of 9–16 MPa; and liquid hourly space velocity of 0.5–2.2 h⁻¹. -1 The hydrogen-to-oil volume ratio is 450:1 to 1200:1. The reaction pressure is the total pressure.
[0047] According to the present invention, the catalyst needs to be sulfided before application. The sulfidation process is as follows: the catalyst is contacted with a sulfidation liquid and hydrogen to undergo sulfidation. The sulfidation liquid includes a solvent and a sulfur-containing solute; the sulfur-containing solute has a mass content of 4.0 wt% to 15.0 wt% in the sulfidation liquid; the sulfur-containing solute is a sulfur-containing compound with a solubility of more than 10 wt% in the solvent at room temperature, and decomposes with hydrogen to produce H2S under high temperature conditions. The sulfur-containing solute includes at least one of carbon disulfide, dimethyl sulfide, dimethyl disulfide (DMDS), and FSA-55 sulfiding agent (developed by Dalian (Fushun) Petrochemical Research Institute of China Petroleum & Chemical Corporation). The solvent is a hydrocracking tail oil component with an initial boiling point of 150℃ to 400℃ and a final boiling point of 400℃ to 550℃. Further, the final boiling point of the hydrocracking tail oil component is higher than its initial boiling point temperature. The solvent may also be a diesel fuel component obtained by hydrocracking, with an initial boiling point of 120℃~250℃ and a final boiling point of 300℃~380℃. The purity of the hydrogen gas is not less than 90% v%.
[0048] According to the present invention, the vulcanization conditions can be conventional vulcanization conditions. Preferably, the vulcanization conditions are as follows: the vulcanization process includes three vulcanization stages. A first isothermal vulcanization stage: heating to 250–260°C and holding at that temperature for 3–8 hours; a second isothermal vulcanization stage: heating to 295–300°C and holding at that temperature for 2–6 hours; a third isothermal vulcanization stage: heating to 315–320°C and holding at that temperature for 1–3 hours. The heating rate to the first vulcanization stage is 10–20.0°C / h, the heating rate to the second vulcanization stage is 8–15.0°C / h, and the heating rate to the third vulcanization stage is 6–10.0°C / h. The flow rate of the vulcanizing liquid is 15–30 mL / (h·g catalyst), the hydrogen pressure is 6.0–18.0 MPa, and the hydrogen flow rate is 80–130 mL / (min·g catalyst).
[0049] Compared with the prior art, the present invention has the following advantages:
[0050] 1. The hydrocracking catalyst of the present invention comprises a support and an active metal component, wherein the support comprises alumina and modified Y molecular sieve; the active metal component comprises Mo and Group VIII metal elements; the Mo comprises +5 valence Mo; the Group VIII metal elements exist in the catalyst in the form of metal phosphides.
[0051] Because the +5 valence molybdenum in the catalyst of this invention is more easily sulfided into +4 valence molybdenum disulfide during the sulfidation process, the rate of molybdenum disulfide formation is accelerated, leading to a greater likelihood of forming Ni-Mo-S(II) and Brim active sites with a MoS2 framework and metallic nickel on the outer surface in the catalyst. The catalyst of this invention also forms a suitable amount of transition metal phosphides, which are compounds formed by phosphorus atoms inserting into the metal lattice and exhibit noble metal-like properties. Due to the large size of phosphorus atoms, after bonding with the transition metal, octahedral coordination structures are more easily formed around the phosphorus atoms, placing them at the central position. Therefore, unlike the layered structure of sulfides, the phosphide structure is closer to a spherical shape, exposing more active sites during the catalytic reaction, making it easier for large molecular reactants to approach the active sites on the catalyst surface. The catalyst support and active metal of this invention work together to exhibit excellent isomerization properties and aromatic hydrocarbon conversion capabilities, making it suitable for hydrocracking processes in the production of specialty oils and lubricating oil base oils.
[0052] 2. In the preparation process of the hydrocracking catalyst of the present invention, the support is first impregnated with an impregnation solution containing molybdenum and sulfur sources to obtain intermediate I, which is then reacted with chlorine gas to obtain intermediate II. Finally, intermediate II is impregnated with a nickel-phosphorus impregnation solution to prepare the catalyst. The support is also prepared using a specific method, namely, the NH4Y molecular sieve filter cake is first hydrothermally treated in the presence of organic acid and water-soluble polymer. This removes non-framework aluminum, increases the silicon-to-aluminum ratio, and improves the pore distribution. The catalyst support is then impregnated in gallium nitrate solution and treated with high-temperature steam, which anchors some gallium species in the support material to form Si-O-Ga bonds. The Ga species effectively prevent the formation of strong Mo(W)-O-Al bonds, thereby weakening the acid regulation and interaction between the active metal and the support, which is beneficial for the hydrocracking catalyst to have a suitable pore structure, acid content, and acid distribution. Through the comprehensive coordination of each step, the catalyst support and active metal work together to significantly improve the isomerization performance and aromatic saturation performance.
[0053] 3. The catalyst of this invention significantly improves isomerization performance and high aromatic saturation performance in the hydrocracking process of base oils for the production of specialty oils and lubricating oils. Detailed Implementation
[0054] The technical solutions and effects of the present invention will be further illustrated by the following embodiments, but the following embodiments do not constitute a limitation on the method of the present invention.
[0055] In this invention, unless otherwise specified, % refers to mass fraction.
[0056] In this invention, the specific surface area, pore volume, and pore distribution are measured using an ASAP2420 fully automated physical adsorption instrument from Micron Instruments, Inc.
[0057] In this invention, the XPS operating conditions are as follows: light source: MgK Alpha, energy step: 0.05 eV, scan range: 220–240 eV (molybdenum), 850–880 eV (nickel), 280–300 eV (carbon). When analyzing the valence state of molybdenum, the binding energy is determined as follows: +6 valence molybdenum species at 232–233 eV, +5 valence molybdenum species at 230–232 eV, and +4 valence molybdenum species at 228–230 eV. The proportions of +6, +5, and +4 valence molybdenum in the total Mo can be calculated using the peak areas of these three peaks.
[0058] In this invention, the mechanical strength is measured using a ZQJ-Ⅲ type particle strength tester manufactured by Dalian Intelligent Testing Machine Factory.
[0059] In this invention, the catalyst composition was determined using spectrophotometry. The testing instrument was a Lambda 365 UV spectrophotometer.
[0060] In this invention, the determination of total infrared acid, L acid or Brønsted acid is performed by infrared spectroscopy, and the instrument used is a Nicot Fourier Transform Infrared Spectrometer-6700 from the United States.
[0061] Example 1
[0062] (1) Preparation of the carrier:
[0063] Take 100g of NaY molecular sieve (properties as follows: molar ratio of silicon dioxide to alumina is 6:1, sodium content is 7wt%), 20g of ammonium chloride and 800g of deionized water, mix and slurry, adjust the pH of the slurry to ≈3.5 with hydrochloric acid, and ion exchange at 90℃ for 2h, with ammonium ion exchange twice. Then filter and wash to obtain NH4Y molecular sieve filter cake; add 1500g of deionized water to the obtained NH4Y molecular sieve filter cake, 3g of citric acid, 20g of polyvinyl alcohol (molecular weight 25000) and stir evenly. Transfer the above material to an autoclave for hydrothermal treatment. After sealing, heat to 100℃ at a rate of 15℃ / min and hold at that temperature for 3 hours. Then heat to 140℃ at a rate of 10℃ / min and hold at that temperature for 6 hours. Filter and wash, and then dry the material at 120℃ for 6 hours to obtain modified molecular sieve.
[0064] 179g of boehmite (alumina content 69.2%), 269g of modified molecular sieve, 9g of guar gum powder, 4.5g of nitric acid, 3g of citric acid, 12g of activated carbon with a particle size of 4 micrometers, and 178g of water were mixed and kneaded into a mold. The mixture was then dried at 120℃ for 3 hours and calcined at 550℃ for 3 hours to obtain catalyst support intermediate A-0. The obtained support intermediate A-0 was then saturated with a 1.5mol / L gallium nitrate solution, kept at 130℃ for 4 hours, and then treated with 100% steam at 550℃ for 90 minutes to obtain catalyst support A-1.
[0065] Catalyst preparation:
[0066] A first impregnation solution was prepared by mixing 63.9 g of ammonium heptamolybdate tetrahydrate, 49.3 g of ammonium sulfide, and water. The molybdenum source in the first impregnation solution contained 29 wt%. The first impregnation solution was then applied to support A-1. The impregnation was saturated. After drying at 100°C for 6 hours in air, catalyst intermediate I was obtained.
[0067] (2) Catalyst intermediate I was reacted with chlorine gas to obtain catalyst intermediate II. The purity of the chlorine gas was 98 v%. The flow rate of the chlorine gas was 3.4 mL / (min·g catalyst intermediate I). The reaction conditions were as follows: reaction temperature was 400℃, and reaction time was 90 min.
[0068] (3) The catalyst intermediate II described in step (2) was impregnated with a second impregnation solution containing nickel and phosphorus sources (35.8 g of nickel nitrate hexahydrate and 8.1 g of diammonium hydrogen phosphate dissolved in water, wherein the mass content of nickel source in the second impregnation solution was 51 wt%). The impregnation was saturated impregnation. After being cured at 25°C for 10 h, dried at 110°C in air for 6 h, and calcined at 510°C in nitrogen for 6 h, the catalyst C1 was obtained.
[0069] The catalyst composition, properties, and pore distribution are shown in Table 2. Group VIII metals exist in the catalyst as metal phosphides. The Mo includes +5, +6, and +4 valence Mo, i.e., Mo exists as molybdenum pentachloride, molybdenum disulfide, and molybdenum oxide. +5 valence Mo accounts for 78.7% of the total Mo atoms, +4 valence Mo accounts for 13.0%, and +6 valence Mo accounts for 8.3%.
[0070] Example 2
[0071] (1) Preparation of the carrier:
[0072] Take 200g of NaY molecular sieve (properties as follows: molar ratio of silicon dioxide to alumina is 4:1, sodium content is 11wt%), 40g of ammonium chloride and 1400g of deionized water, mix and slurry, adjust the pH of the slurry to ≈4 with nitric acid, and ion exchange at 85℃ for 3h, with ammonium ion exchange twice. Then filter and wash to obtain NH4Y molecular sieve filter cake; add the obtained NH4Y molecular sieve filter cake, 6g of citric acid, 20g of methylcellulose (molecular weight 20000) to the above material and add 4000g of deionized water and stir evenly. Transfer the above material to an autoclave for hydrothermal treatment. After sealing, heat to 110℃ at a rate of 10℃ / min and hold at 110℃ for 2.5h, then heat to 130℃ at a rate of 10℃ / min and hold at 130℃ for 6h. Filter and wash; then dry the material at 120℃ for 4h to obtain modified molecular sieve.
[0073] 159g of boehmite (alumina content 68.7%), 229g of modified molecular sieve, 12g of guar gum powder, 6g of nitric acid, 4g of citric acid, 22g of activated carbon with a particle size of 4 micrometers, and 258g of water were mixed and kneaded into a mold. The mixture was then dried at 140℃ for 3 hours and calcined at 550℃ for 3 hours to obtain catalyst support intermediate B-0. The obtained support intermediate B-0 was then saturated with a 2.0mol / L gallium nitrate solution, kept at 120℃ for 5 hours, and then treated with 100% steam at 550℃ for 70 minutes to obtain catalyst support B-1.
[0074] Catalyst preparation:
[0075] A first impregnation solution was prepared by mixing 58.4 g of ammonium heptamolybdate tetrahydrate, 36.5 g of thiourea, and water. The molybdenum source in the first impregnation solution contained 36 wt%. The first impregnation solution was then applied to support B-1. The impregnation was saturated. After drying at 120°C for 4 hours in air, catalyst intermediate I was obtained.
[0076] (2) Catalyst intermediate I was reacted with chlorine gas to obtain catalyst intermediate II. The purity of the chlorine gas was 97 v%. The flow rate of the chlorine gas was 4.8 mL / (min·g catalyst intermediate I). The reaction conditions were as follows: reaction temperature was 400℃, and reaction time was 65 min.
[0077] (3) The catalyst intermediate II described in step (2) was impregnated with a second impregnation solution containing nickel and phosphorus sources (29.2 g of nickel nitrate hexahydrate and 8.1 g of disodium hydrogen phosphate dissolved in water, wherein the nickel source content in the second impregnation solution was 42 wt%). The impregnation was saturated. After being cured at 23°C for 12 h, dried at 120°C in air for 5 h, and calcined at 495°C in nitrogen for 6 h, the catalyst C2 was obtained.
[0078] The catalyst composition, properties, and pore distribution are shown in Table 2. Group VIII metals exist in the catalyst as metal phosphides. The Mo includes +5, +6, and +4 valence Mo, i.e., Mo exists as molybdenum pentachloride, molybdenum disulfide, and molybdenum oxide. +5 valence Mo accounts for 76.9% of the total Mo atoms, +4 valence Mo accounts for 17.0%, and +6 valence Mo accounts for 6.1%.
[0079] Example 3
[0080] (1) Preparation of the carrier:
[0081] Take 152g of NaY molecular sieve (properties as follows: molar ratio of silicon dioxide to alumina is 5:1, sodium content is 7wt%), 46g of ammonium chloride and 1672g of deionized water, mix and slurry, adjust the pH of the slurry to ≈3.5 with nitric acid, and ion exchange at 90℃ for 3h, with ammonium ion exchange twice. Then filter and wash to obtain NH4Y molecular sieve filter cake. Add 3200g of deionized water to the obtained NH4Y molecular sieve filter cake, 5g of adipic acid, 17g of polyvinylpyrrolidone (molecular weight 30000) and stir evenly. Transfer the above material to an autoclave for hydrothermal treatment. After sealing, heat to 110℃ at a rate of 10℃ / min and hold at that temperature for 4 hours. Then heat to 130℃ at a rate of 10℃ / min and hold at that temperature for 6 hours. Filter and wash. Then dry the material at 130℃ for 4 hours to obtain modified molecular sieve.
[0082] 251g of boehmite (alumina content 69%), 336g of modified molecular sieve, 9g of guar gum powder, 4.5g of nitric acid, 3g of citric acid, 17g of activated carbon with a particle size of 4 micrometers, and 328g of water were mixed and kneaded into a mold. The mixture was then dried at 130℃ for 4 hours and calcined at 650℃ for 3 hours to obtain catalyst support intermediate C-0. The obtained support intermediate C-0 was then saturated with a 1.7mol / L gallium nitrate solution, kept at 140℃ for 2 hours, and then treated with 100% steam at 600℃ for 60 minutes to obtain catalyst support C-1.
[0083] Catalyst preparation:
[0084] A first impregnation solution was prepared by mixing 53.9 g of ammonium heptamolybdate tetrahydrate, 46.2 g of sodium thiosulfate, and water. The molybdenum source in the first impregnation solution contained 41 wt%. The first impregnation solution was then applied to support C-1. The impregnation was saturated. After drying at 130°C for 5 h in air, catalyst intermediate I was obtained.
[0085] (2) Catalyst intermediate I was reacted with chlorine gas to obtain catalyst intermediate II. The purity of the chlorine gas was 98 v%. The flow rate of the chlorine gas was 5.3 mL / (min·g catalyst intermediate I). The reaction conditions were as follows: reaction temperature was 350℃, and reaction time was 60 min.
[0086] (3) The catalyst intermediate II described in step (2) was impregnated with a second impregnation solution containing nickel and phosphorus sources (33.4 g of nickel nitrate hexahydrate and 6.1 g of diammonium hydrogen phosphate dissolved in water, wherein the mass content of nickel source in the second impregnation solution was 48 wt%). The impregnation was saturated impregnation. After being cured at 23°C for 12 h, dried at 120°C in air for 6 h, and calcined at 500°C in nitrogen for 7 h, the catalyst C3 was obtained.
[0087] The catalyst composition, properties, and pore distribution are shown in Table 2. Group VIII metals exist in the catalyst as metal phosphides. The Mo includes +5, +6, and +4 valence Mo, i.e., Mo exists as molybdenum pentachloride, molybdenum disulfide, and molybdenum oxide. +5 valence Mo accounts for 76.5% of the total Mo atoms, +4 valence Mo accounts for 16.6%, and +6 valence Mo accounts for 6.9%.
[0088] Example 4
[0089] (1) Preparation of the carrier:
[0090] Take 100g of NaY molecular sieve (properties as follows: molar ratio of silicon dioxide to alumina is 7:1, sodium content is 10wt%), 25g of ammonium chloride and 800g of deionized water, mix and slurry, adjust the pH of the slurry to ≈3.5 with hydrochloric acid, and ion exchange at 90℃ for 2h, with ammonium ion exchange repeated 3 times. Then filter and wash to obtain NH4Y molecular sieve filter cake; add the obtained NH4Y molecular sieve filter cake, 3g of citric acid, 20g of methylcellulose (molecular weight 20000) to the above material and add 1500g of deionized water and stir evenly. Transfer the above material to an autoclave for hydrothermal treatment. After sealing, heat to 100℃ at a rate of 15℃ / min and hold at that temperature for 3 hours. Then heat to 140℃ at a rate of 10℃ / min and hold at that temperature for 6 hours. Filter and wash; then dry the material at 120℃ for 6 hours to obtain modified molecular sieve.
[0091] 224g of boehmite (alumina content 67.8%), 338g of modified molecular sieve, 15g of guar gum powder, 7g of nitric acid, 5g of citric acid, 36g of activated carbon with a particle size of 4 micrometers, and 462g of water were mixed and kneaded into a mold. The mixture was then dried at 120℃ for 3 hours and calcined at 550℃ for 3 hours to obtain catalyst support intermediate D-0. The obtained support intermediate D-0 was then saturated with a 1.5mol / L gallium nitrate solution, kept at 130℃ for 4 hours, and then treated with 100% steam at 600℃ for 80 minutes to obtain catalyst support D-1.
[0092] Catalyst preparation:
[0093] A first impregnation solution was prepared by mixing 56.4 g of ammonium heptamolybdate tetrahydrate, 42.3 g of thiourea, and water. The molybdenum source in the first impregnation solution contained 40 wt%. The first impregnation solution was then applied to support D-1. The impregnation was saturated. After drying at 130°C for 5 hours in air, catalyst intermediate I was obtained.
[0094] (2) Catalyst intermediate I was reacted with chlorine gas to obtain catalyst intermediate II. The purity of the chlorine gas was 99 v% by volume. The flow rate of the chlorine gas was 3.9 mL / (min·g catalyst intermediate I). The reaction conditions were as follows: reaction temperature was 300℃, and reaction time was 80 min.
[0095] (3) The catalyst intermediate II described in step (2) was impregnated with a second impregnation solution containing nickel and phosphorus sources (36.7 g of nickel nitrate hexahydrate and 11.1 g of diammonium hydrogen phosphate dissolved in water, wherein the nickel source content in the second impregnation solution was 53 wt%). The impregnation was saturated. After being cured at 23°C for 12 h, dried at 120°C in air for 6 h, and calcined at 500°C in nitrogen for 7 h, the catalyst C4 was obtained.
[0096] The catalyst composition, properties, and pore distribution are shown in Table 2. Group VIII metals exist in the catalyst as metal phosphides. The Mo includes +5, +6, and +4 valence Mo, i.e., Mo exists as molybdenum pentachloride, molybdenum disulfide, and molybdenum oxide. +5 valence Mo accounts for 78.7% of the total Mo atoms, +4 valence Mo accounts for 15.5%, and +6 valence Mo accounts for 5.8%.
[0097] Example 5
[0098] The difference between this example and Example 1 is that the catalyst support preparation steps are different; other preparation steps are the same as in Example 1. The support preparation steps are as follows:
[0099] Take 100g of NaY molecular sieve (properties as follows: molar ratio of silicon dioxide to aluminum oxide is 6:1, sodium content is 7wt%), 20g of ammonium chloride and 800g of deionized water, mix and slurry, adjust the pH of the slurry to ≈3.5 with hydrochloric acid, and ion exchange at 90℃ for 2h, with ammonium ion exchange twice. Then filter and wash to obtain NH4Y molecular sieve filter cake; add the obtained NH4Y molecular sieve filter cake, 3g of citric acid, 20g of polyvinyl alcohol (molecular weight 25000) to the above material and add 1500g of deionized water and stir evenly. Transfer the above material to an autoclave for hydrothermal treatment, heat to 140℃ at a rate of 10℃ / min and hold at that temperature for 6 hours, filter and wash, and then dry the material at 120℃ for 6 hours to obtain modified molecular sieve.
[0100] 179g of boehmite (alumina content 69.2%), 269g of modified molecular sieve, 9g of guar gum powder, 4.5g of nitric acid, 3g of citric acid, 12g of activated carbon with a particle size of 4 micrometers, and 178g of water were mixed and kneaded into a mold. The mixture was then dried at 120℃ for 3 hours and calcined at 550℃ for 3 hours to obtain catalyst support intermediate E-0. The obtained support intermediate E-0 was then saturated with a 1.5mol / L gallium nitrate solution, kept at 140℃ for 2 hours, and then treated with 100% steam at 550℃ for 90 minutes to obtain catalyst support E-1.
[0101] The catalyst composition, properties, and pore distribution are shown in Table 2. Group VIII metals exist in the catalyst as metal phosphides. The Mo includes +5, +6, and +4 valence Mo, i.e., Mo exists as molybdenum pentachloride, molybdenum disulfide, and molybdenum oxide. +5 valence Mo accounts for 78.3% of the total Mo atoms, +4 valence Mo accounts for 12.3%, and +6 valence Mo accounts for 9.4%.
[0102] Comparative Example 1
[0103] Compared with Example 1, in this example, the NH4Y molecular sieve is directly mixed and kneaded with boehmite and other materials without the addition of organic acids and water-soluble polymers to prepare the carrier. Other steps are the same as in Example 1.
[0104] A comparative hydrogenation catalyst, DCA-1, was prepared. The composition, properties, and pore distribution of the catalyst are shown in Table 2.
[0105] Comparative Example 2
[0106] Compared to Example 2, the only difference is that the catalyst support is not immersed in gallium nitrate solution but undergoes high-temperature steam treatment. The other steps are the same as in Example 1.
[0107] A comparative hydrogenation catalyst, DCA-2, was prepared. The composition, properties, and pore distribution of the catalyst are shown in Table 2.
[0108] Comparative Example 3
[0109] The active metals of the catalyst in this example include molybdenum oxide and nickel phosphide. Compared with Example 1, in the catalyst preparation method, air is used to replace chlorine in step (2) of Example 1, that is, catalyst intermediate I reacts with air. Other steps are the same as in Example 1.
[0110] A comparative hydrogenation catalyst, DCA-3, was prepared. The catalyst composition, properties, and pore distribution are shown in Table 2. The Mo present was in the forms of +6 and +4 valence, but not +5 valence. That is, Mo existed as molybdenum disulfide and molybdenum oxide. +4 valence Mo accounted for 14.2% of the total Mo atoms, and +6 valence Mo accounted for 85.8% of the total Mo atoms.
[0111] Comparative Example 4
[0112] The active metals of the catalyst in this example include molybdenum oxide and nickel oxide. Compared with Example 1, in step (2), air is used instead of chlorine gas in Example 1, that is, catalyst intermediate I reacts with air. In step (3), no phosphorus source is added to the second impregnation solution. Other steps are the same as in Example 1.
[0113] A comparative hydrogenation catalyst, DCA-4, was prepared. The catalyst composition, properties, and pore distribution are shown in Table 2. The Mo present is in the +6 and +4 valence states, and does not contain +5 valence Mo. That is, Mo exists in the form of molybdenum disulfide and molybdenum oxide. +4 valence Mo accounts for 13.8% of the total Mo atoms, and +6 valence Mo accounts for 86.2% of the total Mo atoms.
[0114] Application examples
[0115] The catalysts obtained in the examples and comparative examples were evaluated using the feedstocks listed in Table 3. The properties of the feedstocks and reaction conditions are shown in Table 3, and the evaluation results are shown in Table 4. The catalysts were sulfided before application. The sulfidation conditions were as follows: the sulfidation liquid was hydrocracking tail oil containing 10.0% DMDS by mass. The initial boiling point of the hydrocracking tail oil was 200℃, and the final boiling point was 400℃. The flow rate of the sulfiding liquid was 20.0 mL / (h·g catalyst), the hydrogen pressure was 12.0 MPa, and the hydrogen flow rate was 120.0 mL / (min·g catalyst). The first sulfidation stage started at 25℃ with a heating rate of 10.0℃ / h, and was held at 250℃ for 6.0h. The second sulfidation stage started at 250℃ with a heating rate of 8.0℃ / h, and was held at 300℃ for 4.0h. The third sulfidation stage started at 300℃ with a heating rate of 6.0℃ / h, and was held at 320℃ for 3.0h, at which point the sulfidation was complete.
[0116] Table 1 Properties of the modified Y molecular sieves in each example and comparative example
[0117] Crystal grain size, nm 464 438 392 402 496 657 <![CDATA[SiO2 / Al2O3 molar ratio]]> 26 20 31 36 11 7 <![CDATA[Specific surface area, m 2 / g]]> 706 669 685 710 644 383 Unit cell parameters, nm 2.446 2.463 2.459 2.454 2.436 2.127 Average pore size, nm 12.6 11.8 11.3 12.3 10.4 8.3
[0118] Table 2. Composition and properties of catalysts in each example and comparative example.
[0119]
[0120] Table 3. Properties of feedstock oil and reaction conditions
[0121]
[0122]
[0123] Table 4. Activity evaluation results of each catalyst example.
[0124]
[0125] The specific embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A hydrocracking catalyst, comprising a support and an active metal component, wherein the support comprises a modified Y molecular sieve and alumina, and the modified Y molecular sieve has the following properties: crystal particle size below 500 nm, a molar ratio of silica to alumina of 8-55, and a specific surface area of 640-800 m². 2 / g, with cell parameters of 2.433~2.460nm and average pore size of 10~30nm; The active metal component includes Mo and Group VIII metal elements; in the catalyst, the Mo includes +5 valence Mo; the Group VIII metal elements exist in the catalyst in the form of metal phosphides; The carrier contains Ga, and the Ga content is 2.0% to 5.0% based on the mass of the carrier, calculated as Ga2O3; +5 valence Mo accounts for more than 50% of total Mo atoms; Based on the mass of the catalyst, the mass content of the support is 50% to 90%, the content of Group VIII metals as oxides is 1% to 10%, and the content of molybdenum as oxides is 5% to 40%. The Mo also includes +4 valence Mo and +6 valence Mo; +5 valence Mo is molybdenum pentachloride; +4 valence Mo is molybdenum disulfide; and +6 valence Mo is molybdenum oxide.
2. The catalyst according to claim 1, characterized in that, The crystal particle size of the modified Y molecular sieve is 300~500nm.
3. The catalyst according to claim 1, characterized in that, Based on the quality of the carrier, the content of modified Y molecular sieve is 50%~80%, and the content of alumina is 15%~48%.
4. The catalyst according to claim 1, characterized in that, In the catalyst, +5 valence Mo accounts for 55% to 80% of the total Mo atoms.
5. The catalyst according to claim 1, characterized in that, The sum of +4 valence Mo and +6 valence Mo accounts for 20% to 45% of the total Mo atoms.
6. The catalyst according to claim 1, characterized in that, +4 valence Mo accounts for 10% to 43% of total Mo atoms; +6 valence Mo accounts for 2% to 10% of total Mo atoms.
7. The catalyst according to claim 1, characterized in that, The catalyst has the following properties: specific surface area of 400~750 m². 2 / g, pore volume is 0.3~0.9mL / g, mechanical strength is 120~180N / cm, total infrared acid content is 0.3~0.7mmol / g, and the ratio of B acid content to L acid content is 7.5~15.
2.
8. The catalyst according to claim 1, characterized in that, The catalyst has the following pore size distribution: pores with a diameter <10 nm account for 23%~28% of the total pore volume, pores with a diameter of 10~20 nm account for 38%~45% of the total pore volume, and pores with a diameter >20 nm account for 27%~39% of the total pore volume.
9. A method for preparing the catalyst according to any one of claims 1 to 8, comprising: (1) A first impregnation solution is obtained by mixing molybdenum source, sulfur source and water, and then impregnated on a support. After drying, catalyst intermediate I is obtained. The carrier comprises modified Y molecular sieve and alumina; (2) React the catalyst intermediate I described in step (1) with chlorine gas to obtain catalyst intermediate II; (3) The group VIII metal is selected from nickel. The catalyst intermediate II described in step (2) is impregnated with a second impregnation solution containing nickel source and phosphorus source, and then cured, dried and calcined to obtain the catalyst.
10. The preparation method according to claim 9, characterized in that, The method for preparing the carrier includes: (11) NaY molecular sieve is exchanged with ammonium ions, filtered and washed to obtain NH4Y molecular sieve filter cake; (12) The NH4Y molecular sieve filter cake obtained in step (11) is mixed with organic acid, water-soluble polymer and water, and then subjected to hydrothermal treatment to obtain modified Y molecular sieve; (13) The modified Y molecular sieve, pseudoboehmite, adhesive, pore expander and water obtained in step (12) are mixed and kneaded into shape, dried and calcined to obtain catalyst support intermediate; (14) The catalyst support intermediate obtained in step (13) is immersed in gallium nitrate solution and treated with high temperature steam to obtain the support.
11. The preparation method according to claim 10, characterized in that, The organic acid mentioned in step (12) is selected from at least one of fumaric acid, adipic acid, tartaric acid, citric acid, oxalic acid, acetic acid, salicylic acid and malic acid; And / or, the water-soluble polymer is selected from at least one of polyvinyl alcohol, polyethylene oxide, polyvinylpyrrolidone and water-soluble polysaccharides; the weight-average molecular weight of the water-soluble polymer is 10,000 to 40,000.
12. The preparation method according to claim 10, characterized in that, The NH4Y molecular sieve in step (12) is calculated based on NaY in step (1): the mass ratio of organic acid: water-soluble polymer: water is 1:0.01~0.05:0.05~0.25:15~40; And / or, the conditions for the hydrothermal treatment in step (12) are as follows: temperature is 100~150℃, and treatment time is 5~12h.
13. The preparation method according to claim 10, characterized in that, In step (13), the mass ratio of the pseudoboehmite (calculated as alumina) to the modified Y molecular sieve is (7~13):(15~30). And / or, the roasting temperature in step (13) is 550~700℃ and the roasting time is 2~6 hours.
14. The preparation method according to claim 10, characterized in that, The concentration of the gallium nitrate solution in step (14) is 0.5~2.5 mol / L; And / or, the impregnation method in step (14) is saturated impregnation or unsaturated impregnation; And / or, the conditions for the high-temperature steam treatment in step (14) are as follows: temperature is 500~700℃, and time is 60~90min.
15. The preparation method according to claim 9, characterized in that, In step (2), the purity of the chlorine gas is 96% or higher by volume fraction; And / or, the flow rate of the chlorine gas is 2.7~6.8 mL / (min·g catalyst intermediate I); And / or, the reaction conditions are as follows: reaction temperature is 300~400℃, and reaction time is 40~90min.
16. The preparation method according to claim 9, characterized in that, The nickel source mentioned in step (3) is a soluble nickel salt; And / or, the phosphorus source is selected from at least one of ammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, and phytic acid; And / or, in the second impregnation solution, the molar ratio of nickel source (calculated as metal element) to phosphorus source (calculated as phosphorus element) is 0.3~3:1; And / or, the conditioning described in step (3) is to place the soaked sample under a closed condition of 10~30℃ for 6~12h; And / or, the drying conditions described in step (3) are drying at 100~160℃ for 1~8h; And / or, the calcination conditions described in step (3) are calcination at 480~550℃ for 4~8 hours.
17. The preparation method according to claim 16, characterized in that, The nickel source mentioned in step (3) is at least one selected from nickel nitrate, monohydrogen phosphate, and dihydrogen phosphate.
18. The application of the catalyst according to any one of claims 1 to 8 or the catalyst prepared by the preparation method according to any one of claims 9 to 17 in the hydrocracking process for producing specialty oils and lubricating oil base oils from vacuum distillate oil.
Citation Information
Patent Citations
Hydrocracking catalyst and preparation method thereof
CN102039151A
Preparation method of hydrocracking catalyst
CN103055927A
Residual oil hydrogenation catalyst and preparation method thereof
CN104096584A
Residual oil hydrotreating method
CN114644937A